Pre and Post-Test ECAQ - Shalihin, Mohd Shaiful Ehsan; Wan Mamat, Wan Hasliza; Mohamad Zahir, Mohd Zulkifli; Mohammad Aidid, Edre (2021)
It is the set of questions that need to be answered by the participants before and after the workshop topic ECAQ (Elderly Cognitive Assessment Questionnaire)